2016
DOI: 10.1038/srep26898
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Adhesive Capsulitis of the Shoulder following Cervical Disc Surgery

Abstract: Shoulder problems are common in patients with a cervical herniated intervertebral disc (HIVD). This study aimed to explore the incidence and risk of shoulder capsulitis/tendonitis following cervical HIVD surgery. We used data from the Taiwan “Longitudinal Health Insurance Database”. We identified all patients who were hospitalized with a diagnosis of displacement of a cervical HIVD and who underwent cervical surgery (n = 1625). We selected 8125 patients who received cervical HIVD conservative therapy only as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Again using the Longitudinal Health Insurance Database 2005 in Taiwan, patients who underwent surgery for a cervical herniated disk disease had a markedly higher risk (1.66) of developing shoulder capsulitis in 6-month follow-up compared with patients who received conservative therapy only. 21 Last, though not surgical, worth mentioning is a case study of 3 cases of acute onset of AC after pneumococcal and influenza vaccines. 22 Treatment Options…”
Section: Risk Factorsmentioning
confidence: 99%
“…Again using the Longitudinal Health Insurance Database 2005 in Taiwan, patients who underwent surgery for a cervical herniated disk disease had a markedly higher risk (1.66) of developing shoulder capsulitis in 6-month follow-up compared with patients who received conservative therapy only. 21 Last, though not surgical, worth mentioning is a case study of 3 cases of acute onset of AC after pneumococcal and influenza vaccines. 22 Treatment Options…”
Section: Risk Factorsmentioning
confidence: 99%
“…This condition can often coexist with cervical radiculopathy, hypothesized to be caused by disuse of the rotator cuff muscles or as a progression of the radiculopathy itself 22 . Furthermore, patients who underwent cervical fusion or discectomy, compared with those who were treated with conservative management, are at an increased risk of developing adhesive capsulitis 23 .…”
Section: Cervical Spinementioning
confidence: 99%
“…While there is a well-known relationship regarding the dermatomal overlap of pain pathways in the shoulder joint as originating from either the joint itself or the cervical spine, few studies have evaluated patient-reported outcomes (PROs) after shoulder arthroscopy in patients with concomitant cervical spine pathology. [6][7][8][9][10] Dunn et al 7 demonstrated in an 86,501 patient analysis of prevalence across time that the number of patients with both rotator cuff pathology and cervical spine stenosis has increased significantly in the past decade. Moorthy et al 11 compared outcomes in patients undergoing arthroscopic rotator cuff repair with or without concomitant cervical radiculopathy but found no significant difference in postoperative functional outcomes between the 2 groups.…”
mentioning
confidence: 99%